2020
DOI: 10.3389/fonc.2020.568059
|View full text |Cite
|
Sign up to set email alerts
|

The Resistance Mechanisms of Lung Cancer Immunotherapy

Abstract: Immunotherapy has revolutionized lung cancer treatment in the past decade. By reactivating the host's immune system, immunotherapy significantly prolongs survival in some advanced lung cancer patients. However, resistance to immunotherapy is frequent, which manifests as a lack of initial response or clinical benefit to therapy (primary resistance) or tumor progression after the initial period of response (acquired resistance). Overcoming immunotherapy resistance is challenging owing to the complex and dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(114 citation statements)
references
References 336 publications
0
100
0
3
Order By: Relevance
“…Moderate immune responses to a tumor or their complete absence are explained by the absence of expression of foreign genes in tumor cells. In addition, if the tumor mutation burden, the level of DNA mismatch repair, and genomic microsatellite instability are low, the production of tumor antigens will be reduced, which may lead to drug resistance [69]. This can also cause anatomical isolation of tumor antigens from the immune system (in particular, due to the additional barriers for brain tumors-BBB and BBTB) or generalized immunosuppression in a cancer patient.…”
Section: Immune Evasionmentioning
confidence: 99%
“…Moderate immune responses to a tumor or their complete absence are explained by the absence of expression of foreign genes in tumor cells. In addition, if the tumor mutation burden, the level of DNA mismatch repair, and genomic microsatellite instability are low, the production of tumor antigens will be reduced, which may lead to drug resistance [69]. This can also cause anatomical isolation of tumor antigens from the immune system (in particular, due to the additional barriers for brain tumors-BBB and BBTB) or generalized immunosuppression in a cancer patient.…”
Section: Immune Evasionmentioning
confidence: 99%
“…Epigenetic modifications are associated with anticancer immunity, including T cell function, migration, exhaustion, and neoantigen expression ( Wang et al, 2020 ). Epigenetic modifications silence tumor suppressor and apoptosis genes, thereby activating tumor proliferation ( Table 1 ) ( Baxter et al, 2014 ).…”
Section: Mechanisms Of Acquired Resistance To Anti–pd-1/pd-l1mentioning
confidence: 99%
“…Additionally, another study showed a higher prolonged progression-free survival in anti-PD-1-treated patients harboring TP53 -mut/ STK11 - EGFR -wt tumors than in patients with TP53 -wt/ STK11 -mut [ 111 ]. A few initial studies demonstrated that mutated STK11 tumors, notably with TP53 , KRAS and KEAP1 mutations, showed primary resistance to ICIs [ 15 , 53 , 57 ]. Using whole-exome sequencing to examine NSCLC patients treated with PD-1 plus CTLA-4 blockade, a study demonstrated that a couple of patients with a STK11 mutation had primary resistance to this therapeutic combination [ 6 ].…”
Section: Stk11 As a Predictive Biomarker For Thmentioning
confidence: 99%
“…In line with the tremendous clinical progress, the understanding of the efficacy of immunotherapy in NSCLC and its pathophysiology has unraveled new cellular mechanisms associated with its response to treatment and to intrinsic resistance [ 12 , 13 , 14 , 15 ]. Moreover, bioinformatic analyses are becoming increasingly sophisticated allowing the analysis and integration of complex clinical and biological data to further understand the biology of cancer, notably of lung carcinoma [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%